Integrasi, Komunikasi Komunitas Santri Batang dalam Pencegahan Intoleransi Beragama - Aris Yusuf, Mochamad (CV. Publikasi Indonesia, 2022)
The widespread spread of content of religious intolerance has threatened the unity of the nation's generation, so this condition was responded to by the Batang santri community by spreading content with moderate nuances on social media. The purpose of this study was to determine the integration and communication carried out by the Batang santri community in preventing religious intolerance for youth. This research method uses a qualitative method with an action research approach of Grounded Theory, merged with Max Werber 's theory based on the type of field research. The findings in this study have shown that the efforts made by the Batang santri community in voicing moderate content through social media are effective in preventing the understanding of religious intolerance by young people. According to Max Weber's theory, acting on the basis of saving the younger generation. Integration, Communication of the Batang Santri Community in the Prevention of Religious Intolerance has had a profound impact on the surrounding environment, especially in Batang Regency and the wider community in general. As a forum for young people, the Batang santri community also makes da'wah efforts through Instagram social media.